Analisis Putusan PTUN Medan Nomor 33/G/2023/PTUN.MDN Tentang Pemberhentian Kepala Dinas Perhubungan Sumatera Utara Menurut Persfektif Siyasah Qadha’iyyah - Wilda Ramadhani; Sativa , Annisa (Asosiasi Ide Bahasa Kepri, 2024)
This research aims to analyze aspects of the unilateral dismissal of the Head of the Transportation Service by the Governor of North Sumatra regarding the decision of the Medan State Administrative Court with Number 33/G/2023/PTUN.MDN which arose as a result of a lawsuit against the Governor of North Sumatra which was caused by the issuance of the Governor's Decree with No. 800/0141/BKD/III/I/2023 concerning the Plaintiff being demoted or transferred to become Secretary of the North Sumatra Provincial Manpower Service with a rank or grade down to Echelon III.a. The contents of the Governor's Decree contain the dismissal of Ir. Supriyanto, MM served as head of the Transportation Service located in North Sumatra and he was placed in a new position as Secretary of the North Sumatra Province Manpower Service with a rank or class down to Echelon III.a This research uses library research methods because this research is normative juridical in nature. The result of this decision is to grant all of the applicant's requests to annul and require them to revoke the Decree of the Governor of North Sumatra No. 800/0141/BKD/III/I/2023 which contains the dismissal of Ir. Supriyanto, MM from the position of head of the Transportation Service on January 5 2023. The Governor's decree was declared void because it was deemed to have procedural errors in its issuance. And this research attempts to analyze the principle of siyāsah qaḍhā'iyyah regarding the PTUN's authority in dismissing the Head of the Transportation Service, and how the concept of siyāsah qaḍhā'iyyah is relevant to the authority to dismiss the Head of the Transportation Service through the PTUN's decision.